2008
DOI: 10.1002/pc.20469
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical properties of electron beam irradiated poly(vinyl chloride)/polystyrene blends

Abstract: The effect of electron beam irradiation on the thermal and mechanical properties of poly(vinyl chloride)/polystyrene (PVC/PS) blends and PVC/PS blends containing epoxidized natural rubber (ENR) was studied. The thermogravimetric analysis study showed that the thermal decomposition of the plasticized PVC individual polymer goes through two stages, whereas PS decomposes through one stage. However, the temperature of the maximum rate of reaction (Tmax) of PS is much higher than that for PVC and their blends. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…12 Microorganisms dangerous for human life live in everyday 13 products. Pathogens can exist in various surroundings for a long 14 time without triggering any reactions.…”
Section: Q2mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Microorganisms dangerous for human life live in everyday 13 products. Pathogens can exist in various surroundings for a long 14 time without triggering any reactions.…”
Section: Q2mentioning
confidence: 99%
“…interesting for research [9][10][11][12] TET-Cl was synthesized according to a previously reported method 90 [13] in N-alkylation reaction of poly(4-vinylbenzyl chloride) (MPS-91…”
mentioning
confidence: 99%
“…The effect of electron beam irradiation on the thermal and mechanical properties of PVC/PS blends has been studied by Senna et al [22]. Thermogravimetric analysis showed that the thermal decomposition of PVC goes through two stages, whereas PS decomposes only in one stage.…”
Section: Introductionmentioning
confidence: 99%